Antibacterial Activity Of Neem (Azadirachta indica A. Juss) Essential Oil Obtained By The Enfleuration Method Against Propionibacterium acnes Bacteria In Liquid Soap Formula - Nasution, Rosnani; Bahi, Muhammad; Marianne, Marianne; Hadisah, Dara (Journal of Carbazon, 2025)
This research was conducted to determine the antibacterial activity of Azadirachta indica flower essential oil and its liquid soap formulation against P. acnes bacteria and to determine the quality of the liquid soap formulation. The essential oil of A. indica flower was obtained by the enfleuration method, the yield was a concentrated yellow essential oil with a yield of 2.151%, a density of 0.892 g/mL, solubility in ethanol 90%, 1:1, clear; and a refractive index of 1.435 which complies with the Indonesian National Standard (SNI). Furthermore, essential oils are formulated into liquid soap preparations and tested for physical quality and antibacterial activity. The liquid soap formulation had a distinctive odor of A. indica flowers, and homogen. The antibacterial activity against P. acnes bacteria, was the inhibitory value of A. indica flower liquid soap was higher than A. indica flower essential oil with the highest liquid soap inhibition power of 52%, while the inhibitory power of essential oil was 51% with each concentration of 2.5%, which was compared to its positive control, namely chloramphenicol. The quality testing of liquid soap is accordance with SNI 06-4085-1996, pH values ranging from 8.48 9.67 meet SNI (8-11), viscosity values ranging from 1504.4 cP 2369.7 cP meet SNI (400-4000 cPs), and foam height values ranging from 7.1 cm 8.3 cm. The results of the GC MS analysis of A. indica essential oil showed that the dominant compound was -Copaene (15.84%).